Effect of the iChoose Kidney decision aid in improving knowledge about treatment options among transplant candidates: A randomized controlled trial. Issue 8 (26th March 2018) - Patzer, Rachel E.; McPherson, Laura; Basu, Mohua; Mohan, Sumit; Wolf, Michael; Chiles, Mariana; Russell, Allison; Gander, Jennifer C.; Friedewald, John J.; Ladner, Daniela; Larsen, Christian P.; Pearson, Thomas; et al.
Abstract : We previously developed a mobile‐ and web‐based decision aid (iChoose Kidney) that displays individualized risk estimates of survival and mortality, for the treatment modalities of dialysis versus kidney transplantation. We examined the effect of iChoose Kidney on change in transplant knowledge and access to transplant in a randomized controlled trial among patients presenting for evaluation in three transplant centers. A total of 470 patients were randomized to standard transplantation education (control) or standard education plus iChoose Kidney (intervention). Change in transplant knowledge (primary outcome) among intervention versus control patients was assessed using nine items in pre‐ and postevaluation surveys. Access to transplant (secondary outcome) was defined as a composite of waitlisting, living donor inquiries, or transplantation. Among 443 patients (n = 226 intervention; n = 216 control), the mean knowledge scores were 5.1 ± 2.1 pre‐ and 5.8 ± 1.9 postevaluation. Change in knowledge was greater among intervention (1.1 ± 2.0) versus control (0.4 ± 1.8) patients ( P  < .0001). Access to transplantation was similar among intervention (n = 168; 74.3%) versus control patients (n = 153; 70.5%; P  = .37). The iChoose Kidney decision aid improved patient knowledge at evaluation, but did not impact transplant access. Future studies should examine whether combining iChoose Kidney with other interventions can increase transplantation. (Clinicaltrials.gov NCT02235571) Abstract : The use of iChoose Kidney, a shared decision aid, to educate patients about the survival of transplant versus dialysis is associated with improved patient knowledge about transplantation, but not transplant access among a population of end‐stage renal disease patients presenting for kidney transplant evaluation in a multicenter randomized trial.